Feasibility and effectiveness of two community‐based HIV testing models in rural Swaziland. Issue 7 (2nd April 2015) - Parker, Lucy Anne; Jobanputra, Kiran; Rusike, Lorraine; Mazibuko, Sikhathele; Okello, Velephi; Kerschberger, Bernhard; Jouquet, Guillaume; Cyr, Joanne; Teck, Roger
Abstract Objectives To evaluate the feasibility (population reached, costs) and effectiveness (positivity rates, linkage to care) of two strategies of community‐based HIV testing and counselling (HTC) in rural Swaziland. Methods Strategies used were mobile HTC (MHTC) and home‐based HTC (HBHTC). Information on age, sex, previous testing and HIV results was obtained from routine HTC records. A consecutive series of individuals testing HIV‐positive were followed up for 6 months from the test date to assess linkage to care. Results A total of 9 060 people were tested: 2 034 through MHTC and 7 026 through HBHTC. A higher proportion of children and adolescents (<20 years) were tested through HBHTC than MHTC (57% vs. 17%; P < 0.001). MHTC reached a higher proportion of adult men than HBHTC (42% vs. 39%; P = 0.015). Of 398 HIV‐positive individuals, only 135 (34%) were enrolled in HIV care within 6 months. Of 42 individuals eligible for antiretroviral therapy, 22 (52%) started treatment within 6 months. Linkage to care was lowest among people who had tested previously and those aged 20–40 years. HBHTC was 50% cheaper (US$11 per person tested; $797 per individual enrolled in HIV care) than MHTC ($24 and $1698, respectively). Conclusion In this high HIV prevalence setting, a community‐based testing programme achieved high uptake of testing and appears to be an effective and affordable way to encourage large numbers of people to learn their HIV status (particularly underserved populations such as men and young people). However, for community HTC to impact mortality and incidence, strategies need to be implemented to ensure people testing HIV‐positive in the community are linked to HIV care.